Computed tomographic features of apical infection of equine maxillary cheek teeth: A retrospective study of 49 horses. (18th November 2013) - Bühler, M.; Fürst, A.; Lewis, F. I.; Kummer, M.; Ohlerth, S.
Summary Reasons for performing study Computed tomographic (CT) studies evaluating the relevance of individual CT features of apical infection in maxillary cheek teeth are lacking. Objectives To study the prevalence and relationship of single CT features in horses with and without clinical evidence of apical infection in maxillary cheek teeth. Study design Retrospective case–control study. Methods Multislice CT scans of the head of 49 horses were evaluated retrospectively. Changes of the infundibulum, pulp, root, lamina dura, periodontal space and alveolar bone in maxillary cheek teeth were recorded. Results Single CT changes were much more prevalent in the 28 horses with clinical signs. However, infundibular changes and a nondetectable lamina dura were also common in the 21 horses without clinical evidence of apical infection. Computed tomographic abnormalities of the pulp, root, periapical bone and periodontal space and the presence of a tooth fracture were significantly related. Infundibular changes were not associated with other CT signs of apical infection. Although nondetectable lamina dura was the most frequent CT change in all teeth in both studied groups, it was most commonly a solitary feature in otherwise normal teeth. Apical infections, defined as ≥3 CT changes, occurred mainly in the 108/208, 109/209 and 110/210 (Triadan numbers) and were found only in horses with clinical evidence of apical infection, except in one horse without clinical signs that had one affected root. Conclusions Combined CT changes of the pulp, root, lamina dura, periapical bone and periodontal space and the presence of a tooth fracture appear to be reliable features to diagnose apical infection in maxillary cheek teeth. As a solitary feature, a nondetectable lamina dura should be interpreted cautiously and may even be considered normal due to its minor thickness and/or too low resolution of the imaging modality.